Anoxic Brain Injury: The Abominable Malady - Hrishi, Ajay P.; Prathapadas, Unnikrishnan; Lionel, Karen R.; Puthanveedu, Divya K.; Sethuraman, Manikandan (Journal of Neuroanaesthesiology and Critical Care, 2019)
Anoxic brain injury (ABI) is an important cause of prolonged hospital stay and morbidity across the globe. It is a sequel of major systemic insults resulting from various etiologies, such as reduced oxygen availability, insufficient cerebral blood flow, reduced oxygen carriage, or any metabolic condition that can interfere with the utilization of oxygen. A varying combination of pathophysiologic mechanisms leads to a spectrum of clinical manifestations, the understanding of which will significantly help in prognostication of patients. Neuroprognostication helps both the clinician and the patient's family in planning future course and is further aided by various neuromonitoring modalities, biomarkers, and imaging. Targeted temperature management still remains a therapeutic tool in ABI and along with other neuroprotective measures may improve the survival. Continuing research in ABI may uncover more promising treatment strategies.
Keywords: anoxic brain injury; neuroprognostication; targeted temperature management; hypothermia